Karl Rahner and the Sensus Fidelium - McCann, Pamela (Philosophy & theology, 2013)
This paper explores the contribution of Karl Rahner to theological reflection on the topic of the sensus fidelium and offers his thought as a resource towards rethinking ecclesial norms and praxis in the Roman Catholic Church. Rahner’s reflections bring to the surface a theological value at the heart of revelation, the sensus fidelium, which has remained latent in the Christian tradition. Rahner understood that the People of God as a whole are “Hearers of the Word.” They share the collective responsibility of transmitting revelation from age to age. Rahner understood authoritative teachers of the faith to have a normative role in interpreting God’s revelation; yet the insights and collective faith consciousness of the faithful (sensus fidelium) also provide a legitimate norm for the faith. This work presents Rahner’s thought on the sensus fidelium to show how it is relevant to present-day theological discussion and offers his ideas for integrating the value of the sensus fidelium into the practices of the Catholic Church.